The Effect of Monoglyceride Polymorphism on Cold‐Flow Properties of Biodiesel Model Fuel. (13th July 2017) - Sugami, Yuitsu; Yoshidomi, Shinichiro; Minami, Eiji; Shisa, Noriko; Hayashi, Hitoshi; Saka, Shiro
Abstract: The cloud point (CP) of biodiesel refers to the temperature at which crystallization begins on cooling. However, solid precipitates are often formed at a temperature higher than the CP during storage. Such precipitates are known to consist largely of monoglycerides (MGs) as intermediate compounds. MGs have high melting points, which are detrimental to the cold‐flow properties of biodiesel. MGs have several polymorphic forms, including α, β′ and β, with different melting points (α < β′ < β), and this fact makes the behavior of biodiesel at low temperature complicated. In this study, the precipitation behavior of MGs in biodiesel is discussed focusing on polymorphism using 1‐monopalmitin and methyl oleate mixtures as a model biodiesel fuel. The CPs measured were close to the calculated solid‐liquid equilibrium curve for α‐type 1‐monopalmitin. However, precipitates formed at temperatures higher than the CP when the mixtures were held at temperatures lower than the equilibrium curve of the β′ form. This indicates that the β′ form causes a risk of precipitation at temperatures above the CP and that the CP is not a suitable indicator of the cold‐flow properties of biodiesel.